VD_FINDINFO Décision / 2011 / 761 vom 8. Dezember 2011 - VD Tribunal cantonal (2011)
RISQUE DE RÉCIDIVE, DÉTENTION PRÉVENTIVE | 212 CPP (CH), 221 al. 1 let. c CPP (CH), 396 CPP (CH), 422 al. 1 CPP (CH), 422 al. 2 let. a CPP (CH), 428 al. 1 CPP (CH)